Bioactivity Test of Gambir (Uncaria gambir Roxb) Processing Waste as an Environmentally Friendly Alternative for Pest Control Using Nano Technology - Hamid, Hasmiandy; Reflinaldon, Reflinaldon; Hidrayani, Hidrayani; Yunisman, Yunisman; Lina, Eka Candra (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
The gambir plant can serve as a raw material for botanical insecticides. Plant-based insecticides are made in nanoemulsion form to overcome the insecticide particle size problem. This study aims to obtain a gambir waste form that has the potential to be used as a botanical insecticide using nanotechnology. The laboratory experiments include preliminary and follow-up tests. The preliminary test involves testing each extract (liquid, solid, and raw gambir waste) at three concentrations using a completely randomized design with four replications. The follow-up test uses the residue method on leaves to test insecticidal activity. Creating nanoemulsion from gambir waste involves mixing organic and liquid phases through spontaneous emulsification. The insecticidal effectiveness of this nanoemulsion is tested on Croccidolomia pavonana. The results show that solid and liquid gambir waste has the potential to be used as alternative insecticides, which can influence the mortality of C. pavonana with an LC50 concentration of 0.22 (solid waste) and 0. 29 (liquid waste), while LC95 is 2.44 (solid waste) and 2.52 (liquid waste). The research promotes utilizing natural resources and innovative technologies, advancing environmentally conscious pest control methods, and fostering sustainable agricultural systems.